Reverse Transcriptase PCR (Rt-PCR) for Detection of Dengue and Chikungunya Virus of Mosquito Aedes aegypti in Sokaraja - Annisa, Dyah Retno; Kusmintarsih, Endang Srimurni; Ambarningrum, Trisnowati Budi (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
dengue fever (DF). Meanwhile, chikungunya virus causes Chikungunya fever (CF). These diseases involve three organisms, namely virus, mosquito Aedes sp., and human. The transmission of dengue and chikungunya virus is related to the population of Ae. aegypti. Banyumas regency is one of the regions with many cases of dengue and chikungnya virus infections, particularly in Purwokerto, Sokaraja, and Cilongok sub-district. Up to this time, there is no medicine and vaccine provided to treat these viruses effectively. Thus, detection of virus inside vector will be effectively performed in order to predict the transmission risk of dengue and chikungunya virus. This research aimed to know the molecular detection of dengue and chikungunya virus on adult Ae.aegypti mosquito in Sokaraja Region, Banyumas Regency. Survey was done by a cross-sectional method in Sokaraja sub-district from May 2019 – March 2019. Furthermore, technical sampling that used was purposive sampling method of adult Ae.aegypti using BG-Sentital Trap, followed by molecular detection of dengue virus using Two-step RT-PCR and chikungunya gene virus using RT-PCR. Molecular detection of DENV and CHIKV of mosquitoes which collected from Sokaraja region showed negative result